A Framework for Australian Universities and Public Libraries Supporting Regional, Rural and Remote Students. Issue 4 (2nd October 2021) - Partridge, Helen; Power, Emma; Ostini, Jenny; Owen, Sue; Pizzani, Blanca
ABSTRACT: University students living in regional, rural and remote (RRR) communities of Australia face unique challenges including geographical isolation, lack of access to face-to-face support, and technological barriers. This paper outlines a project funded by the Australian Government's Higher Education Participation and Partnerships Program that was undertaken by five universities with significant enrolments of students from low socio-economic backgrounds living in RRR communities. The project established a Framework for Australian Universities and Public Libraries Supporting Regional, Rural and Remote Students that provides a set of strategic recommendations that will guide the development of accessible, relevant and sustainable study and learning support to meet the needs of low socio-economic students living in RRR communities. This national project provided a unique opportunity for Australia's universities and public libraries to work together in order to 'future proof' the education of students from low socio-economic backgrounds living in regional and remote communities.